The Bright Elusive Butterfly of Value in Health Technology Development; Comment on "Providing Value to New Health Technology: The Early Contribution of Entrepreneurs, Investors, and Regulatory Agencies" - Trisha Greenhalgh; Nick Fahy; Sara Shaw (Kerman University of Medical Sciences, 2018)
The current system of health technology development is characterised by multiple misalignments. The "supply" side (innovation policy-makers, entrepreneurs, investors) and the "demand" side (health policy-makers, regulators, health technology assessment, purchasers) operate under different - and conflicting - logics. The system is less a "pathway" than an unstable ecosystem of multiple interacting sub-systems. "Value" means different things to each of the numerous actors involved. Supply-side dynamics are built on fictions; regulatory checks and balances are designed to assure quality, safety and efficacy, not to ensure that technologies entering the market are either desirable or cost-effective. Assessment of comparative and cost-effectiveness usually comes too late in the process to shape an innovation's development. We offer no simple solutions to these problems, but in the spirit of commencing a much-needed public debate, we suggest some tentative ways forward. First, universities and public research funders should play a more proactive role in shaping the system. Second, the role of industry in forging long-term strategic partnerships for public benefit should be acknowledged (though not uncritically). Third, models of "responsible innovation" and public input to research priority-setting should be explored. Finally, the evidence base on how best to govern inter-sectoral health research partnerships should be developed and applied.